Examining the K-5 Teachers’ Perceptions towards Teaching: Traditional and Constructive Approaches - Salahuddin, Muhammad; LeMire, Steven D. (CenRaPS Journal of Social Sciences, 2024)
Teachers’ views, classroom behaviors, and the learning environment are important for students learning. This study assessed teachers’ attitudes toward traditional and constructive teaching and learning concepts. Survey data was collected from 692 in-service teachers at government primary schools through a self-reported Likert-type data collection instrument. Quantitative analysis revealed that most teachers believe in a constructive teaching-learning approach in Bangladesh. However, teachers’ previous educational qualifications considerably influenced their teaching and learning concepts. Teachers with post-secondary degrees believe in constructive teaching-learning approaches more than traditional teaching-learning concepts. Therefore, it would be beneficial that attempts are made to improve teacher education from Higher Secondary School Certificate (HSC) to Honours or master’s level to achieve constructivist teaching in the classroom.